Digital prevention of depression for farmers? A qualitative study on participants' experiences regarding determinants of acceptance and satisfaction with a tailored guided internet intervention program - Freund, Johanna; Buntrock, Claudia; Braun, Lina; Thielecke, Janika; Baumeister, Harald; Berking, Matthias; Ebert, David; Titzler, Ingrid (Internet Interventions, 2022)
Introduction: Farmers, forest workers and gardeners have a higher risk of developing depression compared to other occupational populations. As part of the German pilot project "With us in balance", the potential of six guided internet- and mobile-based interventions (IMIs) to prevent depression among their insurants is examined. The IMI program is tailored to various risk factors of depression, individual symptoms, and needs. Although IMIs have been shown to be effective in reducing depressive symptoms, there is little qualitative research about the acceptance of digital preventive IMIs. The aim of this qualitative study is to gain insights into participants' experiences with the guided IMIs by focusing on determinants for acceptance and satisfaction.
CRIS-Team WoS Importer:2022-09-02